Keaktivan Belajar Siswa Kelas XI Ditinjau Dari Fasilitas Ruang Kelas Dan Strategi Mengajar Guru Di Sekolah Menengah Atas 2 Sukoharjo Tahun Ajaran 2014/2015 - Dewi, Hanifah Kumala, Drs. Djumali, M.Pd (2015)
ABSTRACT KEAKTIVAN LEARNING CLASS XI VIEWED FROM CLASSROOM FACILITIES AND STRATEGIES TEACHING HIGH SCHOOL TEACHER IN THE STATE 2 SUKOHARJO ACADEMIC YEAR 2014/2015 Hanifah Kumala Dewi, A 210 110 132, Accounting Education Study Program, the Faculty of Education, University of Muhammadiyah Surakarta, 2015. The purpose of this study was to determine: 1) To determine the influence of classroom facilities for students of class XI keaktivan SMAN 2 Sukoharjo academic year 2014/2015. 2) To determine the effect of the teacher's teaching strategies keaktivan students of class XI SMAN 2 Sukoharjo academic year 2014/2015. 3) To determine the influence of classroom facilities and teaching strategies of teachers to students of class XI keaktivan SMAN 2 Sukoharjo academic year 2014/2015. This research includes associative quantitative research whose conclusions obtained based on the statistical analysis. The population in this study were all students of class XI IPS in SMAN 2 Sukoharjo, amounting to 130 students, and a sample of 95 students obtained by simple random sampling technique. Data collection techniques with methods of questionnaires and documentation. Previous questionnaire has been tested-piloted with validity and reliability. The data analysis technique used to test the hypothesis is multiple linear regression analysis, t test and F test, test R2, and the relative contribution and effective contribution. Results of regression analysis regression equation Y = 14.545 + 0,234X1 + 0,383X2 which means students' learning activeness influenced by classroom facilities and teaching strategies teachers. Conclusion: 1) There is an effect keaktivan classroom facilities for students' learning. Based on test results obtained t t> t table, namely 2.060> 1.9860 (α = 5%) and a significance value <0.05, namely 0.042. 2) There is the influence of teachers 'teaching strategies for students' learning activeness. Based on test results obtained t t> t table, namely 4.456> 1.9860 and significance value <0.05, namely 0.000. 3) There is the influence of classroom facilities and teaching strategies keaktivan teacher to student learning. Based on test results obtained value F Fhitung> Ftable is 11.813> 3.10 and a significance value <0.05, namely 0.000. 4) Variable classroom facilities contribute effectively amounted to 3.468%, the variable teaching strategies teachers contribute effectively amounted to 16.932%, the total effective contribution amounted to 20.4%, so it can be said that the strategy of teachers to teach more dominant keaktivan student learning. 5) The result of the coefficient of determination (R2) of 0.204 indicates that the influence of classroom facilities and teaching strategies of teachers to student learning keaktivan was 20.4% with the remaining 79.6% is influenced by other variables. Keywords: Facilities classrooms, teachers' teaching strategies, student learning keaktivan